Examining the Relationship Between Sport Passion and Mental Resilience Levels of Sport Sciences Faculty Students - Serdar CEYHUN; Sevim Handan YILMAZ; Gökhan DOKUZOĞLU; Pınar KARACAN DOĞAN (ümit doğan üstün, 2023)
As sports competition intensifies, the importance of athletes being mentally prepared becomes increasingly prominent, alongside their physical readiness. Mental toughness is a key component that greatly characterises this notion of preparedness. The purpose of this study was to investigate the correlation between the intensity of sports passion and the level of mental resilience among students studying in the faculty of sports sciences. The study was structured using the relational scanning model, and data collection was conducted through a survey comprising three sections. The initial section encompasses demographic data, the subsequent section encompasses the Sports Mental Toughness Inventory, and the final section encompasses the Sports Passion Scale. The data was disseminated to the participants through Google forms following the acquisition of ethical authorizations, and their voluntary participation in the research was duly considered. The research group comprises 310 students from Aydın Adnan Menderes University, consisting of 138 females and 172 males. The selection of participants was done using a convenient sampling method. Statistical analyses were conducted, including frequency and percentage calculations, reliability coefficient calculations, correlation analysis, hierarchical regression analysis, and Manova analysis. The research findings revealed a correlation between the confidence and continuity sub-dimensions of mental toughness in sports and the sub-dimensions of passion in sports. Additionally, there was a significant difference in the participants' gender, weekly sports frequency, and sports history variables. The research findings indicate that when students studying at the faculty of sports sciences have a strong and balanced passion for sports, their participation in sports aligns with their personal values and other aspects of their lives. Additionally, the participants' level of mental endurance influences their level of passion for sports. Furthermore, it can be asserted that there is no notable disparity in the levels of mental resilience and enthusiasm for sports among students enrolled in the faculty of sports sciences based on the participants' age. Moreover, as the duration of participants' engagement in sports activities increases, their levels of self-assurance, command, and consistency also rise, consequently leading to an enhancement in their mental endurance levels. Participants who engage in sports 1-2 days a week can be considered more adaptable compared to other participants. Conversely, individuals who engage in sports daily tend to exhibit a higher level of obsession compared to those who spend less time on sports.